Women's economic empowerment through Nugraha Women Farmer Group: An initiative fostered by the agricultural extension agency in Cirumput Village, Sukabumi Regency - Siti Raysa; Pratiwi Amalia (Tamalanrea: Journal of Government and Development (JGD), 2025)
The Nugraha Women Farmers Group (KWT) located in Selaawi Village, Sukaraja District, Sukabumi Regency, is a form of village women's institution engaged in the processing of agricultural products. Established in 2002 under the guidance of the Agricultural Extension Agency (BPP) of Sukaraja District, KWT consists of 32 women who are active in producing chips, selling rice, and managing various foods based on local agricultural products. This study aims to examine the role of KWT Nugraha in empowering women's economy through post-harvest activities, as well as identifying obstacles faced in the aspects of institutional development and member participation. The method used is a descriptive qualitative approach through interviews, observations, and documentation. The results of the study show that KWT Nugraha contributes to increasing household income and strengthening women's social solidarity. However, challenges still arise, such as the weak sustainability of coaching from extension workers, low business literacy, and lack of mastery of technology and market access. Group activities tend to be passive if they are not driven by administrators or external parties. This study recommends the need for strengthening the capacity of administrators, ongoing training, and support for village policies that favor women's economies based on local institutions.